2014
DOI: 10.1177/1534734613520324
|View full text |Cite
|
Sign up to set email alerts
|

Free-Style Dual Plane Recycling Tensor Fascia Lata Musculocutaneous Perforator Flap for Reconstruction of Recurrent Trochanteric Defects

Abstract: Sequential flap coverage might be required for recurrent defects, but reusing a flap as a donor site has seldom been reported. The concept of a "free-style flap" has been developed, and it allows reconstructive surgeons to raise flaps with various designs reliably, even at sites of previous flap surgery. This article presents the concept of free-style recycling of a tensor fascia lata flap into a perforator-based flap separated in 2 planes in a patient with a recurrent bilateral trochanteric defect. If a relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The use of a previous redundant flap as a donor site is an interesting alternative in this situation [ 11 17 ]. Valauri et al [ 12 ] reported the case of a patient who sustained bilateral below-knee amputations that were treated with skin grafts as initial coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a previous redundant flap as a donor site is an interesting alternative in this situation [ 11 17 ]. Valauri et al [ 12 ] reported the case of a patient who sustained bilateral below-knee amputations that were treated with skin grafts as initial coverage.…”
Section: Discussionmentioning
confidence: 99%
“…It derives its blood supply from the lateral circumflex nutrient artery, well documented for its reliability and consistency. 3537 Traditionally, the flap is used for abdominal and trochanteric defects, 3841 and generally its use is associated with little donor-site morbidity and loss of function. It is reported that the “safe dimensions” for the flap extends from the pedicle artery to 8–10 cm above the knee and should be no wider than 15 cm 29,42 ; however, Saito et al 43 required skin grafts to primarily close all 9 donor sites in their study, despite the flap being less than 10 cm in some of their patients.…”
Section: Discussionmentioning
confidence: 99%